Iowa Birdline update, May 30, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for May 30, 1989. Highlights include Western Kingbirds, Least Terns and a Piping Plover. Epson - sheet feed/flatbed